2005
DOI: 10.1200/jco.2005.02.1329
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Tumor Regression After Preoperative Chemoradiotherapy for Rectal Cancer

Abstract: In this exploratory analysis, complete (TRG 4) and intermediate pathologic response (TRG 2 + 3) suggested improved DFS after preoperative CRT. TRG assessment should be implemented in pathologic evaluation and prospectively validated in further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
790
10
29

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,112 publications
(861 citation statements)
references
References 34 publications
32
790
10
29
Order By: Relevance
“…Pathological complete tumour response is a reliable and reproducible surrogate for tumour response and is linked to improved outcome (Roh et al, 2004;Roedel et al, 2005). Although achievement of a pCR is not the primary goal of neoadjuvant therapy, it has become a commonly used end point in many phase II trials aiming to improve the efficacy of rectal cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological complete tumour response is a reliable and reproducible surrogate for tumour response and is linked to improved outcome (Roh et al, 2004;Roedel et al, 2005). Although achievement of a pCR is not the primary goal of neoadjuvant therapy, it has become a commonly used end point in many phase II trials aiming to improve the efficacy of rectal cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The number of tumour-infiltrated lymph nodes (ypN status) following preoperative radiochemotherapy is a strong and independent prognostic factor for survival. Sterilising lymph nodes reflects the impact of effective neoadjuvant treatment and consistently translates into improved long-term outcome (Bouzourene et al, 2002;Chan et al, 2005;Chapet et al, 2005;Roedel et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the phase II study, we have analysed the pathologic response using the TRG score, because it has been shown to be more accurate in defining the tumour regression after primary therapy, and to predict the long-term outcome (Bouzourene et al, 2002;Rödel et al, 2005;Vecchio et al, 2005). Notably, the number of TRG1 or 2 required by our statistical design had already been reached in the first 31 treated patients, with an overall activity (71%) by far greater than that hypothesised.…”
Section: Discussionmentioning
confidence: 99%
“…Phase II We have chosen as primary end point the achievement of a complete or nearly complete pathologic response, because it has been repeatedly reported to predict the long-term survival of patients (Bouzourene et al, 2002;Rödel et al, 2005;Vecchio et al, 2005). To define the sample size, a Simon's two-stage design was utilised (Simon, 1989), setting a and b errors as 0.05 and 0.20, and defining as minimum activity of interest (p0) a TRG1 -2 rate ¼ 30%.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 In addition, the tumor regression grade (TRG) characterization of the pathologic response has shown to be a prognostic factor for local failure, metastasis-free and overall survival with significant better outcome for patients reporting TRG 1-2 (absence or scattered residual isolated cancer cells) compared with those reporting TRG 3-5 (increase in the number of residual cancer cells). 11,12 Nonetheless, TRG 3 could be considered an intermediate prognostic status and some investigators suggested a three-point classification system (TRG 1-2, TRG 3 and TRG 4-5) as a good predictor of pCRT outcome in rectal cancer. 13 For patients with pathologic complete response after pCRT, some investigators advocate an observational approach without any surgical treatment, 14 and others suggest that the transanal local excision may be appropriate.…”
Section: Introductionmentioning
confidence: 99%